PREGNANCY OUTCOME AFTER RELATED KIDNEY TRANSPLANTATION (CLINICAL CASE) - Алена Васильевна Иванникова; Елена Валентиновна Гришкевич; Елена Николаевна Орлова; Елена Владимировна Рудаева; Светлана Ивановна Елгина; Кира Борисовна Мозес; Наталья Степановна Черных (Мать и дитя в Кузбассе)
Women of childbearing age with end-stage renal disease have fertility rates that are almost 10 times lower than healthy women. Kidney transplantation significantly improves reproductive function in such patients, increasing their fertility by about four times compared to dialysis. Fertility is restored within a few months after transplantation, and safe conception can probably be achieved as early as one year after transplantation. Preconception counseling, family planning, and contraception are an integral part of the care of women planning pregnancy after kidney transplantation.